The Study Of Entreprenuers, Entreprenuership, Incubators And The Services And Facilities Of Two Main Technology/University Incubators In Malaysia - Ramish Nair, M.P.B @ Lee Rui Bing (2005)
The thesis deals with the measuremnt of the importance and performance of the services, facilities, qualification, skills and experience provided by the Incubator Management Team as well as the incubatees satisfaction of the overall services and quality of facilities offered in the Malaysian University/Technology Incubators.